Pheophorbide a May Regulate Jasmonate Signaling during Dark-Induced Senescence - Aubry, Sylvain (Plant Physiol, 2020)
Chlorophyll degradation is one of the most visible signs of leaf senescence. During senescence, chlorophyll is degraded in the multistep pheophorbide a oxygenase (PAO)/phyllobilin pathway. This pathway is tightly regulated at the transcriptional level, allowing coordinated and efficient remobilization of nitrogen toward sink organs. Using a combination of transcriptome and metabolite analyses during dark-induced senescence of Arabidopsis (Arabidopsis thaliana) mutants deficient in key steps of the PAO/phyllobilin pathway, we show an unanticipated role for one of the pathway intermediates, i.e. pheophorbide a. Both jasmonic acid-related gene expression and jasmonic acid precursors specifically accumulated in pao1, a mutant deficient in PAO. We propose that pheophorbide a, the last intact porphyrin intermediate of chlorophyll degradation and a unique pathway “bottleneck,” has been recruited as a signaling molecule of chloroplast metabolic status. Our work challenges the assumption that chlorophyll breakdown is merely a result of senescence, and proposes that the flux of pheophorbide a through the pathway acts in a feed-forward loop that remodels the nuclear transcriptome and controls the pace of chlorophyll degradation in senescing leaves.